Discovery, design, and synthesis of indole-based EZH2 inhibitors. Issue 17 (1st September 2015) - Gehling, Victor S.; Vaswani, Rishi G.; Nasveschuk, Christopher G.; Duplessis, Martin; Iyer, Priyadarshini; Balasubramanian, Srividya; Zhao, Feng; Good, Andrew C.; Campbell, Robert; Lee, Christina; Dakin, Les A.; Cook, Andrew S.; et al.
Graphical abstract